Design, fabrication, and testing of a low frequency MEMS piezoelectromagnetic energy harvester. (20th February 2018) - Fernandes, Egon; Martin, Blake; Rua, Isabel; Zarabi, Sid; Debéda, Hélène; Nairn, David; Wei, Lan; Salehian, Armaghan
Abstract: This paper details a power solution for smart grid applications to replace batteries by harvesting the electromagnetic energy from a current-carrying wire. A MEMS piezoelectromagnetic energy harvester has been fabricated using PZT screen-printing technology with a centrally-supported meandering geometry. The energy harvesting device employs a symmetric geometry to increase its power output by reducing the effects of the torsional modes and the resultant overall strain nodes in the system subsequently reduce the complexities for the electrode fabrication. The unit is modelled using COMSOL to determine mode shapes and frequency response functions. A 12.7 mm by 14.7 mm unit is fabricated by screen-printing 75 μ m-thick PZT on a stainless steel substrate and then experimentally tested to validate the FEA results. Experimentally, the harvester is shown to produce 9 μ W from a wire carrying 7 A while operating at a distance of 6.5 mm from the wire. The design of the current work results in a greater normalized power density than other MEMS based piezoelectromagnetic devices and shows great potential relative to larger devices that use bulk or thin film piezoelectrics.